Evaluating the Adequacy of MODIS in the Assessment of Drought (Case Study: Urmia Lake Basin) - Mohammadhusayn Rezaeimoghadam; Khalil Valizadeh Kamran; Hashem Rostamzadeh; Ali Rezaee (جغرافیا و پایداری محیط)
Drought is a complex phenomenon with different effects. Hence, the indicators are used to determine the intensity and vastity of the drought. Using remote sensing science, we can study Drought over its effects on plants and Agriculture and achieve more precise and influential results for drought Modeling. In this research, evaluations of function of the MODIS data in estimating the drought in the Urumia lake basin from 2000 to 2011 was examined. Data from Terra-MODIS Satellite (for May the first) and Monthly precipitation data (from February to April) were also used in this process. Furthermore, VCI and TCI indexes were studied in this research. VCI was obtaibed through NDVI, and NDVI, in turn, was assessed from 13 and 16 bavds respectively. Also to get TCI, Brightness Temperature of band 31 was used and maps of drought from 2000 to 2011 were obtained for these indexes too. As the results of these two indexes were different, SPI was used to determine the functions in a 3month duration in 2011. The VCI and TCI figures in 2011 were extracted from the images and the Pearson correlation among them was concluded. VCI correlation with the SPI is 0.7 and TCI correlation with SPI is 0.25. The level of VCI significance was acceptable too. According to the results, VCI and MODIS images can be good substitutions for meteorological indexes to estimate the drought and since satellite images have more advantages over meteorological approaches such as the more sampling points, wider coverage, higher temporal resolution (separation) and lower costs, the use of remote sensing is proposed.